Osteochondrosis (Osteochondritis Dissecans) in Lusitano Horses: Prevalence and Characteristics - Ramos, Sofia (2022)
Osteochondrosis (osteochondritis dissecans), OC(D), is an important joint disorder that has been stud- ied through the years in different breeds but, to our knowledge, there are no reports of its prevalence in Lusitano horses. The aim of this study was to assess the prevalence of OC(D) in Lusitanos, define the characteristics of the disorder in this breed and compare with Spanish Purebred horses. This is a retrospective study that analysed the radiographs from the metacarpometatarsophalangeal, tarsocrural and femoropatellar joints that were taken in 302 Lusitano horses (1–12 years; obtained from 2007 until 2019). The classification of the radiographs for OC(D) was performed using a 0–4 scale and scored by three veterinarians. Radiographical evidence of OC(D) was diagnosed in 53.3% of the horses examined. Most of the findings were lesions of score 1 or 2 corresponding to flattening, (36.8%). The distal interme- diate ridge of the tibia in the tarsocrural joint was the most affected predilection site (31.0%, n=187/604 joints assessed). Overall, the tarsocrural joints were more likely to be affected, followed by metatarso- metacarpophalangeal joints and finally the femoropatellar joints. The prevalence of horses with scores 3 or 4 (fragments) in any of the joints was 16.6%. A positive correlation was found between the scores of contralateral joints. We can conclude that the prevalence of OC(D) in Lusitano horses is similar to the prevalence in Spanish Purebred, but there is a lower percentage of fragmentation. The present phenotypic description can provide valuable information for further quantitative and molecular genetic studies.